Anticoagulation Therapy in Patients with Venous Thromboembolic Disease - Whittle, Jeff (Blackwell Science Inc, 1998)
OBJECTIVE: To determine, in a representative sample of patients drawn from a variety of hospitals, the degree of adherence to consensus recommendations for anticoagulation among patients with deep vein thrombosis or pulmonary embolism. DESIGN: Cross-sectional review of a population-based random sample. SETTING: Twenty-one randomly selected Pennsylvania hospitals. PATIENTS: Of 357 randomly selected Medicare beneficiaries discharged from study hospitals with a diagnosis of deep venous thrombosis or pulmonary embolism during 1992, 43 charts were not reviewed for administrative reasons, 31 were miscoded or not treated with intravenous administration of heparin, and 13 were excluded for other reasons, leaving 270 in the final sample. MEASUREMENTS AND MAIN RESULTS: Overall, 179 patients (66%, 95% confidence interval [CI] 59%, 72%) received therapeutic anticoagulation (two consecutive partial thromboplastin times more than 1.5 times control) within 24 hours of starting heparin. Platelet counts were checked at least once during the first week of heparin therapy in 66% (95% CI 58%, 74%). At least 5 days of heparin therapy was given to 84% (95% CI 79%, 87%). Among 266 (99%) of the patients receiving warfarin, 193 (72%; 95% CI 63%, 80%) received heparin until the prothrombin time ratio or International Normalized Ratio was therapeutic. Patients who were started on warfarin therapy within 2 days of heparin had decreased length of stay (geometric mean 8.2 vs 9.7 days, p = .003). Compliance varied among hospitals. CONCLUSIONS: In a wide variety of hospitals, we found fair, but variable, compliance with consensus recommendations for anticoagulation of patients with venous thromboembolic disease. Simple interventions to improve compliance with these recommendations might improve quality of care and reduce costs.